PedsQLTM Asthma Module - Short Form 22: tradução, adaptação transcultural e avaliação de indicadores psicométricos da versão brasileira - Alves, Raquel Emanuele de França Mendes (2018)
Objectives: To translate, transculturally adapt and evaluate the psychometric indicators of the Brazilian version of the PedsQLTM Asthma Module - Short Form 22. Materials and methods: An exploratory study carried out in two stages: linguistic validation and evaluation of the psychometric indicators of the instrument. Clinical control (Childhood Asthma Control Test (c-ACT) and Asthma Control Test (ACT)); health-related quality of life (HRQOL) (Pediatric Asthma Quality of Life Questionnaire (PAQLQ) e PedsQLTM Asthma Module) and spirometry were used for evaluation. The feasibility, reliability, and reproducibility of the measurements obtained with the Brazilian version of the instrument were evaluated through the floor and ceiling effect, Cronbach's alpha coefficient and test-retest (subgroups "with change" and "without change"), respectively. The construct validity was evaluated by the exploratory factorial analysis (EFA) and the concurrent by the correlation between the adapted Brazilian version and PedsQLTM Asthma Module, PAQLQ, c-ACT/ACT and FEV1 and FEV1/FVC. Results: The first step included 57 participants (26 patients between 5 to 18 years and 31 parents/guardians). All items of the questionnaire were clear and understandable (agreement ranging from 0.78 to 1.00). In the pre-test (n = 57), no participants had difficulty understanding. In the second step participated 234 individuals, of which 117 were patients between 2 to 18 years and 117 parents/guardians. The Brazilian version of the instrument had an internal consistency of 0.83 and 0.77 for the version of children/adolescents and parents/guardians, respectively. In its structure were pre-determined 03 factors of orthogonal rotation (varimax) were identified for each domain (asthma symptoms and treatment problems) in the children/adolescents and parents/guardians’ versions to which they explained an adequate cumulative total variance. The main HRQOL indicators of children/adolescents with asthma were those related to shortness of breath, emotional function and difficulties in adhering to treatment. Conclusion: The Brazilian version of the PedsQLTM Asthma Module SF22 questionnaire was able to provide valid and reliable measures for the assessment of the HRQOL of children/adolescents with asthma.